Are women with advanced pelvic organ prolapse treated by open mesh sacrocolpopexy at risk of secondary incisional hernia?. Issue 11 (November 2015) - Alhalabi, Feras; Bacsu, Chasta; Gulpinar, Omer; Scott, Daniel; Zimmern, Philippe
Abstract Introduction Our purpose was to determine whether vaginal hernia is a predisposing factor for incisional hernia (IH) in a cohort of women with symptomatic pelvic organ prolapse (POP) who underwent corrective repair by open mesh sacrocolpopexy (MSC) and had long-term follow-up to determine their rate of subsequent IH. Methods Following IRB approval, the charts of women entered into a longitudinal database and who underwent open MSC at a tertiary institution were reviewed. Data collected included demographics, MSC and IH details, and long-term outcome. Patients were excluded if the follow-up after MSC was < 1 year. Data were reviewed by a neutral investigator who was not involved in patient care (FA). Results From 1999 to 2012, 75 of 88 women met inclusion criteria, with mean follow-up of 65 (48–84) months. Thirteen were either lost to follow-up or had follow-up < 1 year. Seven women underwent symptomatic IH repair, with a mean onset of IH diagnosis after MSC at 18 (range 8–72) months. Five repairs were done via an open approach, and two were repaired laparoscopically. No IH recurrence was noted at a mean of 41 (range 14–75) months after IH repair. No risk factors were identified in the IH group compared with those who did not form a secondary IH. Conclusions In this longitudinal series, IH after open MSC occurred in 9.3 %, a rate comparable with that reported in women undergoing abdominal procedures through midline or Pfannenstiel incisions.